Design and development of electronic stethoscope for auscultation - Munir, Sahrul; Endiyono, Endiyono (Universitas Muhammadiyah Purwokerto, 2021)
Background: Currently, several companies offer Bluetooth-based electronic stethoscopes. However, the stethoscopes are pretty overpriced. In this case, we need a stethoscope innovation with a more affordable price that carries the same function and improves ear sensitivity during auscultation of heart and lung sounds.Technic: This stethoscope is equipped with a condenser mic that functions as a sound catcher on the stethoscope membrane. The analog data of the condenser mic is regulated by the potential of the pre-amp mic amplifier; then, analog data is forwarded using Bluetooth 5.0 A2DP BT600 USB Wireless Audio Transmitter and received by Bluetooth receiver using earphones.Conclusion: A electronic stethoscope has been successfully developed, which can function adequately to detect, increase heart, lung, bowel sounds, and prenatal sounds.